Nasal Septum Perforation Associated to Histoplasmosis: A Retrospective Study - Jacinto Pineda; Rommie Merino-Alado; Sofia Mata-Essayag; Maria Eugenia Landaeta; Liseloth Garrido; Maria del Mar Rosas (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the prevalence of nasal septum perforation associated to Histoplasma sp. Material and Methods: A retrospective descriptive study was conducted with patients who developed nasal septum perforation associated to histoplasmosis. The diagnosis was made based on clinical manifestations and confirmed with mycological direct examination with Giemsa stain, culture, serologic tests (immunodiffusion method), and histopathology with hematoxylin-eosin, Grocott methenamine (GMS) and Periodic Acid-Schiff stain (PAS). Results: Out of 1654 medical records reviewed with diagnosis of histoplasmosis in the study period, we found 22 cases with nasal septum perforation. Autoimmune disease was present in 6 patients; all six were on immunosuppressive treatment. Two patients had HIV/AIDS, one of them had also paracoccidiodomycoses and the remaining had no apparent underlying disease or conditions. Conclusion: Physicians of endemic areas such as Venezuela, must consider this entity in the differential diagnosis with other diseases.